2018
DOI: 10.1186/s40814-018-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for the collection of electronic PROMS either “in clinic” or “at home” as part of the PROMs, PREMs and Effectiveness Programme (PPEP) in Wales: a feasibility study using a generic PROM tool

Abstract: BackgroundThe patient-reported outcome measures (PROMs), patient-reported experience measure (PREMs) and Effectiveness Programme (PPEP) launched with the aim of supporting all National Health Service Wales (NHS Wales) organisations to collect PROMs and PREMs across a range of conditions. The aim is to collect generic and condition-specific PROMs and PREMs electronically from every secondary care patient in Wales to provide a measure that can be used to determine the clinical and cost-effectiveness of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…Similar to other literature, this review highlighted the importance of investing time in designing the PROMs process] and tailoring it to the specific context by considering the needs and opinions of patients and clinicians [ 40 ]. This review identified that it was useful to involve clinicians in designing the PROMs process and this has been identified in other studies [ 41 ]. From both this review and wider literature it is evident that organisations not only need to design how to administer PROMs, but also consider how clinicians should interpret and act on the data generated].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other literature, this review highlighted the importance of investing time in designing the PROMs process] and tailoring it to the specific context by considering the needs and opinions of patients and clinicians [ 40 ]. This review identified that it was useful to involve clinicians in designing the PROMs process and this has been identified in other studies [ 41 ]. From both this review and wider literature it is evident that organisations not only need to design how to administer PROMs, but also consider how clinicians should interpret and act on the data generated].…”
Section: Discussionmentioning
confidence: 99%
“…23 In-clinic or at-home completion could take place prior to a consultation to help inform this patientclinician decision-making process, allowing tailoring of treatment plans to match an individual's response and preference and providing a framework to identify treatment outcomes which otherwise could go unrecognised. 11 The tool as currently designed calls for assessment at a moment in time 24 which may be coterminous with a medical outpatient review. It is recognised that measurement over a period of time is recommended in line with the measurement of constructs such as psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In these circumstances, an approach which focuses on patient‐reported outcome measures (PROMs) and patient‐reported experience measures (PREMs) may be more appropriate to inform future TMAU treatment outcomes pre‐ and post‐intervention . PROMs and PREMs are reported to narrow the gap between the clinician's and patient's view of clinical reality as they participate in the design of care delivery themselves, a process which is also known as co‐production and sees patients and clinical staff as equal partners to optimise the best outcome for each individual patient's journey …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to PROMs, there has been an increasing interest in the collection of Patient Reported Experience Measures (PREMs) . PREMs are surveys designed to capture patient experience of care and are used as a means of engaging patients in their care pathway, measuring the quality of services provided, informing improvement actions, and evaluating performance of services delivered.…”
Section: Introductionmentioning
confidence: 99%